Pandangan Maqashid Syari’ah tentang Harta Bersama Pasca Perceraian pada Status Perkawinan Semenda pada Masyarakat Adat Lampung Saibatin di Kecamatan Batu Brak - Fikriyah, Kunidhurotul; Syukur, Iskandar; Qodir Zaelani, Abdul (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This study examines the concept of joint property division after divorce within the semenda marriage system of the Lampung Saibatin customary community, where the husband resides in the wife’s family environment. This socio-cultural arrangement influences ownership, control, and distribution of marital assets, often creating imbalances when separation occurs. Using a qualitative socio-legal approach and the framework of maqāshid al-sharīʿah, this research analyzes how Islamic legal principles align with or diverge from customary practices. Data were collected through field observations, interviews with customary and religious leaders, and analysis of secondary literature and legal documents. The findings reveal that Lampung Saibatin’s semenda practice recognizes shared property but lacks standardized procedures for its division after divorce. The maqāshid al-sharīʿah perspective particularly hifẓ al-māl (protection of wealth), hifẓ al-nasl (protection of lineage), and hifẓ al-ʿirdh (protection of dignity) offers an integrative solution to ensure fairness and gender equity. It recommends that property distribution should not be strictly equal but proportional to each party’s contribution and social responsibility. Harmonizing Islamic law and local custom through mediation, prenuptial agreements, and recognition of non-monetary contributions can achieve substantive justice and preserve social harmony in the Lampung Saibatin community.